A one‐year prospective study on alveolar ridge preservation using collagen‐enriched deproteinized bovine bone mineral and saddle connective tissue graft: A cone beam computed tomography analysis. (28th August 2019) - Seyssens, Lorenz; Eghbali, Aryan; Christiaens, Véronique; De Bruyckere, Thomas; Doornewaard, Ron; Cosyn, Jan
Abstract: Background: Although there is ample research on alveolar ridge preservation (ARP), changes of the soft tissue profile are seldom reported. In addition, the use of a saddle connective tissue graft (S‐CTG) has only been described in one study. Purpose: To evaluate changes in bone and external soft tissue profile following ARP of intact and nonintact sockets using collagen‐enriched deproteinized bovine bone mineral (C‐DBBM) and a S‐CTG (a); to assess the need for additional hard and soft tissue grafting after ARP (b). Materials and Methods: Patients in need of a single or multiple unit fixed reconstruction in the premaxilla were included in this prospective case series. After tooth extraction, sockets were grafted with C‐DBBM and sealed with a S‐CTG. Cone beam computed tomography slides taken before tooth extraction and 4 to 6 months after ARP were superimposed to measure changes in bone dimensions and external soft tissue profile. The need for additional hard and soft tissue grafting was registered. Implants were evaluated at 1 year. Patient‐reported outcomes were registered on a 100 mm visual analogue scale at suture removal and 1 year following ARP. Results: Nineteen teeth (10 with intact sockets, 9 with nonintact sockets) in 14 patients (11 females; mean age 34) were extracted and treated with the abovementioned protocol. Volume loss could not be prevented and mainly occurred at the buccal aspect. Maximum horizontal bone resorption was 1.27 mm and maximum horizontal shrinkage of the soft tissue profile amounted to 0.87 mm, both at the most cervical aspect. Additional GBR was necessary in two sites with a nonintact buccal bone wall. The need for additional soft tissue grafting was moderate in sites with intact (3/10) and high in nonintact sockets (6/9). Implants demonstrated favorable clinical and esthetic outcomes. Pain intensity and patient satisfaction were 17 and 94, respectively. Conclusion: Alveolar ridge preservation was not able to prevent relevant tissue changes. However, implants could be installed as planned. Although the application of a S‐CTG partly compensated for the buccal bone loss, the need for additional soft tissue grafting was still moderate in intact sockets and high in nonintact sockets.